A content analysis of religion and HPV vaccine news coverage in Canada - Xiaohe Sun; Tyler Sun; Sharlane C. L. Lau; Allison McArthur; Ishani Nath; Gilla K. Shapiro (Human Vaccines & Immunotherapeutics, 2025)
Human papillomavirus (HPV) can cause several cancers. In Canada, HPV vaccination is publicly funded, yet uptake has not consistently reached coverage targets. Media reporting on the perspectives of religious leaders may impact vaccine behavior; however, there has been limited exploration of media depictions of religious perspectives of HPV vaccination in Canada. This study examined the content and tone of news media’s depiction of religion and HPV vaccination in Canada. To identify news reports for our content analysis, we searched Canadian Newsstream, Global Newsstream, and Factiva for English language news articles between 2006 and 2024. Published articles covered a 13-year period (2006–2018); no articles were found between 2019 and 2024. We coded 333 articles for: (1) publication information, (2) article tone, (3) description of religious leaders’ or members’ views toward HPV vaccination, (4) voices represented, and (5) HPV vaccination content reported. Most articles adopted a neutral (72%) or positive (23%) tone toward HPV vaccination. Most articles (97%) focused on Catholic perspectives, with minimal inclusion of other faiths. The most frequently quoted voices in the articles were from school board trustees or administrators (46%), religious leaders (45%), and healthcare professionals (43%). In the articles, medical professionals (68%) and community leaders (45%) were frequently cited as endorsing the HPV vaccine, while religious leaders were less often cited as endorsing vaccination (14%). Support for the vaccine by religious leaders or members primarily focused on disease prevention, while opposition often centered on concerns about promoting sexual activity and misalignment with religious values. As HPV vaccination policies evolve, including endorsement from interfaith leaders and other stakeholders may be important for inclusive health journalism, accurate portrayal of wide-ranging religious perspectives, and the public health priority to increase HPV vaccination.